Democracy in crisis in Latin America: Bolivia and Venezuela test the international community's democratic commitment - Günther Maihold; Jörg Husar (Stiftung Wissenschaft und Politik (SWP), 2005)
Bolivia appears to be over the worst of its current crisis, now that parliament has accepted President Carlos Mesa's resignation and early elections are in prospect. Mesa held the office of president from October 2003 to June 2005 after Gonzalo Sánchez de Losada was toppled and fled to the United States after just 14 months in office. Mesa's resignation and the decision to hold new elections have initially succeeded in calming feelings in a strongly polarized civil society, but any elected successor to the appointed interim President Eduardo Rodríguez will face the same dramatic challenges. Democracy in Bolivia - and in other nearby countries in the Andes region - is heading for a crucial test that could become a great danger for the whole continent. The same also applies to Venezuela, whose leader President Hugo Chávez champions a 'Bolivarian ideology of integration' for Latin America that involves a fundamentally different model of democracy.(SWP Comments / SWP)
Keywords: 320